HISTOPATHOLOGIC PATTERN OF OVARIAN TUMORS IN VARIOUS AGE GROUPS - Khan, Mir Attaullah; Shah, Hamid Ullah; Qayyum, Abdul; Khan, Ejaz Hassan (Journal of Postgraduate Medical Institute, 2017)
Objective: To study the histopathologic pattern of ovarian tumors in different age groups. Methodology: This retrospective study was conducted on 300 cases with histopathologically proven ovarian tumors reported in histopathology section of Department of Pathology, Lady Reading Hospital (LRH) Peshawar, from 1st January 2011 to 31st December 2015. All the patients operated at LRH or somewhere else by any surgical procedure, but their specimens being processed in histopathology section of LRH, were included in the study. Autolysed specimens and those with unremarkable histologic findings were excluded from the study. For histopathological patterning, classification system of the World Health Organization (WHO) for ovarian tumors was applied. Hematoxylin and eosin stains were used for histological study of the tissues. Results: During the study period, 300 specimens of ovarian tumors were received in the department of Pathology LRH Peshawar. Mean age of the patients was 35.2 ±7.46 years ranging from 6-70 years. Eighty three percent (250) tumors were benign, 1.7% (5) were borderline and 15% (45) were malignant. Most common (80%) tumors of both benign and malignant origin were surface epithelial tumors followed by germ cell tumors (18.7%). Benign surface epithelial tumors comprised 80% (200/250) of all benign tumors whereas their malignant counterparts comprised 78% (35/45) of all malignant tumors. Conclusion: Among the histomorphologic variants of ovarian tumors, benign tumors are more common than malignant ones for all age groups. Surface epithelial tumors are the most common tumors out of both benign and malignant classes. Benign tumors are common in young age below 40 years while malignant ones are common above 40 years of age.